Paul Hindemith's Symphony in B flat and Septet: a conductor's analysis - Morin, Chase, author; Phillips, Rebecca, advisor; Grapes, K. Dawn, committee member; Kenney, Wesley, committee member; Mallette, Dawn, committee member (Colorado State University. Libraries, 2016)
The Symphony in Bb and Septet by Paul Hindemith are cornerstone works in the wind repertory. The conductor’s analysis of these works is a resource and a tool that includes a biographical sketch covering the major events in Hindemith’s life, an outline of the composer’s compositional style, a detailed analysis of the formal components of each work, and specific issues that require consideration when planning rehearsals. With this tool, the conductor who intends to study and conduct these works will find information that is vital to the preparation required to create an authentic performance. This body of information can be a source for discovering new ideas and analyses or to substantiate ideas and information that have been acquired either from other sources or by the conductor himself.